2020
DOI: 10.1148/radiol.2020201697
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI Findings in Patients in the Intensive Care Unit with COVID-19 Infection

Abstract: Online supplemental material is available for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
285
5
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(331 citation statements)
references
References 17 publications
21
285
5
13
Order By: Relevance
“…An updated literature search for studies published between July 30, 2020 and October 9, 2020 resulted in 346 studies, of which seven studies met the same eligibility criteria [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Overall, 21 articles with a total of 2125 patients were included [ 4 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. No additional eligible study was found after a search of references within the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An updated literature search for studies published between July 30, 2020 and October 9, 2020 resulted in 346 studies, of which seven studies met the same eligibility criteria [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Overall, 21 articles with a total of 2125 patients were included [ 4 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. No additional eligible study was found after a search of references within the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies, all study designs were retrospective, except for two prospective studies [ 28 , 39 ]. Nine studies were multi-center studies [ 4 , 29 , 31 , 33 , 36 , 38 , 40 , 42 , 43 ] whereas the other 12 were performed at single centers [ 27 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 , [44] , [45] , [46] ]. The cohort sizes ranged from 9 to 454 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…67,68 A Turkish study showed that 12/27 patients (44%) showed abnormalities on brain MRI with signs suggestive of ischemia or menigoencephalitis. 69 Of note, only minimal evidence points to direct infection of neurons/glial cells by SARS-CoV-2 viral particles, as shown by mostly negative RT-PCR analyses from CSF (Table S7). 53,64,66 Nevertheless, CSF from a small subset of patients with encephalitic features did test positive for SARS-CoV-2 RNA.…”
Section: Neurological Complicationsmentioning
confidence: 99%